2016
DOI: 10.3390/molecules21101339
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Mitigates Cadmium Stress by Regulating Glutathione Levels and Reactive Oxygen Species Homeostasis in Tobacco Seedlings

Abstract: Abstract:Thymol is a famous plant-derived compound that has been widely used in pharmacy due to its antioxidant and antimicrobial properties. However, the modulation of intrinsic plant physiology by thymol remains unclear. It is a significant challenge to confer plant tolerance to Cd (cadmium) stress. In the present study physiological, histochemical, and biochemical methods were applied to investigate thymol-induced Cd tolerance in tobacco (Nicotiana tabacum) seedlings. Thymol was able to alleviate Cd-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…Similar to APX, GPX can also reduce H 2 O 2 . Regeneration of GSH could be achieved by reducing GR, and GSH is an antioxidant that can improve plant tolerance to environmental stresses, such as those posed by HMs (Jia et al 2016;Ye et al 2016). Under Cd exposure, our results indicate that GPX and GR activities significantly up-regulated in parallel with an increased expression of GR compared with CK, indicating that tobacco leaves may improve the tolerance to Cd by enhancing the GSH-GSSG cycle.…”
Section: •-mentioning
confidence: 67%
“…Similar to APX, GPX can also reduce H 2 O 2 . Regeneration of GSH could be achieved by reducing GR, and GSH is an antioxidant that can improve plant tolerance to environmental stresses, such as those posed by HMs (Jia et al 2016;Ye et al 2016). Under Cd exposure, our results indicate that GPX and GR activities significantly up-regulated in parallel with an increased expression of GR compared with CK, indicating that tobacco leaves may improve the tolerance to Cd by enhancing the GSH-GSSG cycle.…”
Section: •-mentioning
confidence: 67%
“…The fluorescence was observed and captured with a fluorescence microscope (ECLIPSE, TE2000-S, Nikon, Melville, NY, USA) with setting of excitation 480-490 nm/emission 515-525 nm for green fluorescence (DCFH-DA and HPF) and excitation 530-540 nm/emission 610-620 nm for red fluorescence (DHE and PI). Histochemical staining of leaves was performed based on our previous study (Ye et al 2016). O 2…”
Section: Histochemical Analysismentioning
confidence: 99%
“…The relative abundance of house-keeping gene Actin was used as the internal standard to normalize the expression data. The detailed procedure can be found in our previous study (Ye et al 2016). The final expression data was clustered and presented as heatmap using Cluster 3.0 combined with Java Treeview (Shi et al 2014).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…[27] It is classified by the Food and Drug Administration, as being generally recognized as safe (GRAS). [28] Moreover, a number of studies showed that thymol reduced the key mediators of inflammation, such as cyclooxygenase (COX-2)catalyzed prostaglandin E2 (PGE2), [29] as well as inflammatory cytokines like nuclear factor kappa B (NF-κB), TNF-α, and IL-1β. [30,31] It also reduced gastric and colon inflammation induced by ethanol and acetic acid, respectively, in previous studies.…”
mentioning
confidence: 99%